PATRIARCH JOSEPH SLIPYJ AND ECUMENISM - BILOVUS, Lesia; HOMOTIUK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
The study addresses the topic of Ukrainian church unity through the lens of Patriarch Josyf Slipyi’s activity and creativity, drawing on materials from Ukrainian-language periodicals in the United States. This aspect is not sufficiently covered in the modern scientific discourse; the refore, it needs analysis. The life of Josyf Slipyi is an example of how it is possible to actively organize and lead the Ukrainian community in the entire world. The Ukrainian Greek Catholic Church began to cultivate and develop the ideas of ecumenism at the very beginning of the 20th century, even before the Edinburgh World Missionary Conference of 1910, which was clearly manifested in the ecumenical activity of Patriarch Josyf Slipyi. The work for the unity of the Churches becomes a driving force in his life as a priest and hierarch, especially after hisre turn from Roman captivity. The Ukrainian Greek Catholic Church decided to restore unity with Rome back in the 16th century, and given its history and religious tradition, it is in a unique position to help bridge the gap between Catholic and Orthodox Christianity. The Velehrad congresses, in which Josyf Slipyi participated, highlighted the issue of church unity in a new way. This is what was discussed later at the Second Vatican Council. The works «The Importance of St. Thomas for the Cause of Unification», «Byzantinism as a Form of Culture», «The Petrograd Synod of 1917», and «A View of the United and Ununited Churches of the East and Dogmatic Differences Between Them» reveal Josyf Slypyi’s ecumenical views and position. Josyf Slypyi did not take the position of achieving the unity of the Orthodox and Catholic Churche sat any cost. He considered both churches to be of equal status. The Patriarch criticized those who believed that it was possible to achieve the unity of the Church by human reason in gand all kinds of manipulations. After his release in 1963, Josyf Slypyi came to Rome, emphasizing the «ecumenism of the martyrs». During the meeting of the Second Vatican Council, Metropolitan Josyf presented the project for the creation of the Kyiv-Halytskyi Patriarchate, a vision of which he developed in the 1930s. The constitution «On Liturgies» was promulgated, and the decree «On Ecumenism» was adopted. However, the message of Josyf Slypyi, «On Unity in Christ», is considered the most ecumenical. In the search for the revival of the Eastern tradition, Josyf Slypyi did not prefer the search for differences and alienation but rather mutual relations and respect, because one must not forget that the influence of the Churches of the West and the East was mutual. Now is a difficult, but at the same time favorable period for ecumenism, because when a new political and economic context comes, we will be ready to offer the governments of Ukraine and other countries a new ideology: the vision of the Kyiv church, communion, the existence of separate states that are friends through spiritual connections. Understanding between Ukrainian Christians will help Ukrainian storestore their identity, freed from historical divisions, pluralistic but united. In today's independent Ukraine, ecumenism will be a guarantee of national unity.